2021
DOI: 10.1038/s41467-021-26460-z
|View full text |Cite
|
Sign up to set email alerts
|

Lung mesenchymal stromal cells influenced by Th2 cytokines mobilize neutrophils and facilitate metastasis by producing complement C3

Abstract: Pre-metastatic niche formation is critical for the colonization of disseminated cancer cells in distant organs. Here we find that lung mesenchymal stromal cells (LMSCs) at pre-metastatic stage possess potent metastasis-promoting activity. RNA-seq reveals an upregulation of complement 3 (C3) in those LMSCs. C3 is found to promote neutrophil recruitment and the formation of neutrophil extracellular traps (NETs), which facilitate cancer cell metastasis to the lungs. C3 expression in LMSCs is induced and sustained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 60 publications
3
68
0
Order By: Relevance
“…Interestingly, the C3 production by MSCs is stimulated by Th2 cytokines. 149 Hence, the secreted factors by MSCs may serve as the essential signals to remodel the tumor microenvironment.…”
Section: Major Factors Released By Mscsmentioning
confidence: 99%
“…Interestingly, the C3 production by MSCs is stimulated by Th2 cytokines. 149 Hence, the secreted factors by MSCs may serve as the essential signals to remodel the tumor microenvironment.…”
Section: Major Factors Released By Mscsmentioning
confidence: 99%
“…Specifically, the class 2 tumors were more active in terms including nucleotide excision repair, DNA repair, base excision repair, DNA replication, mismatch repair and homologous recombination (Fig 4c). In addition, like LUAD, the infiltration score of Th2 cells which promoted tumor immune evasion and metastasis in class 2 tumors were also dramatically higher than class 1 tumors in pan-cancer (Fig 4c) [21-23].…”
Section: Resultsmentioning
confidence: 99%
“…55 A recent study found that targeting the Th2-STAT6-C3-NET (neutrophil extracellular trap) signalling axis effectively inhibited breast cancer metastasis to the lungs. 56 Another study reported that p53 mutations may promote malignancy in solitary fibrous tumours by regulating the NAB2-STAT6 fusion gene at the transcriptional level. 57 Thus, in the future, other signalling pathways regulated by PRKCSH or Nano ZnO in lung cancer should be investigated further.…”
Section: Discussionmentioning
confidence: 99%